The house on Mango Street - Cisneros, Sandra (New York : Vintage Books, 1991)
For Esperanza, a young girl growing up in the Hispanic quarter of Chicago, life is an endless landscape of concrete and run-down tenements, and she tries to rise above the hopelessness
The house on Mango Street -- Hairs -- Boys & girls -- My name -- Cathy queen of cats -- Our good day -- Laughter -- Gil's furniture bought & sold -- Meme Ortiz -- Louie, his cousin & his other cousin -- Marin -- Those who don't -- There was an old woman she had so many children she didn't know what to do -- Alicia who sees mice -- Darius & the clouds -- And some more -- The family of little feet -- A rice sandwich -- Chanclas -- Hips -- The first job -- Papa who wakes up tired in the dark -- Born bad -- Elenita, cards, palm, water -- Geraldo no last name -- Edna's Ruthie -- The Earl of Tennessee -- Sire -- Four skinny trees -- No speak English -- Rafaela who drinks coconut & papaya juice on Tuesdays -- Sally -- Minerva writes poems -- Bums in the attic -- Beautiful & cruel -- A smart cookie -- What Sally said -- The monkey garden -- Red clowns -- Linoleum roses -- The three sisters -- Alicia & I talking on Edna's steps -- A house of my own -- Mango says goodbye sometimes.
Keywords: Mexican Americans -- Fiction; Girls -- Fiction; Chicago (Ill.) -- Fiction; Bildungsromane